Penerapan pembelajaran Discovery Learning untuk meningkatkan prestasi belajar matematika siswa kelas V SDN 02 Donowangun - Novita Ragilia (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to examine the improvement of student learning outcomes through the application of discovery learning. The subjects in this study were grade 5 students at SDN 02 Donowangun, Talun. Based on the results of the study, in the first cycle the percentage of learning completeness was 52% and the average student learning outcome was 73, meaning that in the first cycle it did not meet the overall learning completeness criteria. While in the second cycle the percentage of learning completeness was 89.5% and the average student learning outcome was 85, meaning that in the second cycle it met the criteria for learning completeness as a whole. The activeness of students in the application of discovery learning in the first cycle met the moderate criteria, while the second cycle as a whole met the high criteria, meaning that there was an increase in student activity and collaboration in the application of discovery learning. The percentage of teacher skills in learning by using discovery learning increased from 80% in the first cycle to 87.5% in the second cycle with the high category.